Luboržákite, Mn2AsSbS5, a new member of pavonite homologous series from Vorontsovskoe gold deposit, Northern Urals, Russia. (10th October 2020) - Kasatkin, Anatoly V.; Makovicky, Emil; Plášil, Jakub; Škoda, Radek; Agakhanov, Atali A.; Stepanov, Sergey Y.; Palamarchuk, Roman S.
Abstract: Luboržákite, ideally Mn2 AsSbS5, is a new mineral from the Vorontsovskoe gold deposit, Northern Urals, Russia. It forms long-prismatic crystals up to 70 × 20 μm and anhedral grains of the same size embedded in the matrix of Mn-bearing dolomite and Mn-bearing calcite. Associated minerals include pyrite, orpiment, realgar, stibnite, aktashite, alabandite, boscardinite, chabournéite, coloradoite, clerite, écrinsite, gold, routhierite, sphalerite and twinnite. Luboržákite is black, opaque with metallic lustre and has a black streak. It is brittle and has an uneven fracture. No cleavage and parting have been observed. Mohs hardness is 4–4½. D calc = 4.181 g cm –3 . In reflected light, luboržákite is tin-white, weakly anisotropic with rotation tints varying from dark grey to grey. The chemical composition of luboržákite is (wt.%; electron microprobe, WDS mode): Mn 21.23, Cu 0.29, Ag 0.56, Pb 1.90, As 15.25, Sb 27.03, S 33.23, total 99.49. The empirical formula based on the sum of all atoms = 9 apfu is Mn1.86 Pb0.04 Ag0.03 Cu0.02 As0.98 Sb1.07 S5.00 . The new mineral is monoclinic, space group C 2/ m with a = 12.5077(6), b = 3.8034(2), c = 16.0517(8) Å, β = 94.190(4)°, V = 761.57(6) Å 3 and Z = 4. The crystal structure of luboržákite was solved from the single-crystal X-ray diffraction data to R = 0.0383 for 712 observed reflections with I > 3σ( I ). Luboržákite is a new member of the heterochemical isostructural series of 'unit-cell twinned' structures, named the pavonite series. The new mineral honours Lubor Žák, a prominent Czech crystallographer and the professor of the Charles University in Prague, Czech Republic.